Analysis of oceanic features from dual-polarization high resolution X-band SAR imagery for oil spill detection purposes - Velotto, Domenico; Lehner, Susanne; Soloviev, Alexander; Maingot, Chris (International Geoscience and Remote Sensing Symposium (IGARSS), 2012)
Most part of the sea oil pollution is caused by unintentional and intentional discharges from ships and offshore platforms. Being a serious threat of the marine ecosystem, tools that offer wide area coverage and 24h/day monitoring capabilities are needed. In this way, Synthetic Aperture Radar (SAR) has become an operational instrument to contrast deliberate oil releases and to monitor areas affected by oil accident. © 2012 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: biogenic slicks; dual-pol Synthetic Aperture Radar (SAR) data; oil slick; oil spill; ship wakes; TerraSAR-X